ANATOMY OF A MIGRAINE: Conflict and Tension in the South Asian Collectivity - Mathur, Saloni (Culture, 1990)
This article addresses the theme of internal differences among South Asian television producers in Canada. Not only is “South Asian culture” internally contested in the arena of broadcasting, but this can be related to a long history of contestation (over ethnicity, religion, language and culture) that extends well beyond the context of contemporary Canada. The cultural claims of the Fijian community (demanding more air-time and their own show), and the political demands made by a society of Sikhs (demanding the termination of a producer because of her political stance), represent only two of the conflicts generated through broadcasting. Further, these tensions are played out in front of the CRTC, through cable companies, and complex corporate and regulatory environments. Drawing from recent trends in critical theory, I explore some of the political and theoretical problems associated with the representation of radical difference, and the “real” heterogeneity of Canadian lives. These issues are discussed in relation to the present ideological context of “Multiculturalism”, and in terms of emergent postmodern discourses of difference and “otherness”, of authority and domination, as critical moments within the academy.